Updates in Liver Cancer 2017
DOI: 10.5772/66139
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Optimization of the Future Liver Remnant

Abstract: Safe liver resection is a vital element in the management of primary and secondary hepatic malignancies. The indications for resection have evolved Over time, and this has in part been due to the ability to improve the future liver remnant (FLR). This chapter reviews the current and future methods used for assessing the future liver remnant volume and function in order to minimize the risk of post-hepatectomy liver failure (PHLF). Current and evolving methods used in augmenting the future liver remnant are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Various embolizing agents are available, like n-butyl cyanoacrylate and ethiodized oil, fibrin glue, ethanol, and microparticles, such as polyvinyl alcohol or trisacryl gelatin. While there are no randomized studies available comparing the agents, a review by Maundura and Koea [15] showed that in terms of an increase in the FLR, n-butyl cyanoacrylate was a better agent. The degree of liver hypertrophy depends upon the condition of the FLR.…”
Section: Portal Vein Embolizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various embolizing agents are available, like n-butyl cyanoacrylate and ethiodized oil, fibrin glue, ethanol, and microparticles, such as polyvinyl alcohol or trisacryl gelatin. While there are no randomized studies available comparing the agents, a review by Maundura and Koea [15] showed that in terms of an increase in the FLR, n-butyl cyanoacrylate was a better agent. The degree of liver hypertrophy depends upon the condition of the FLR.…”
Section: Portal Vein Embolizationmentioning
confidence: 99%
“…In the case of a normal liver, an FLR of at least 20% is considered optimal. If the patient has received previous chemotherapy for more than 12 weeks, the optimal FLR is 30%, while in patients with cirrhosis, it should be more than 40% [15]. Although various methods are available to augment the FLR, like PVE, Associating Liver Partition and Portal Vein Ligation with Staged hepatectomy (ALPPS), portal vein ligation, Assessment of Liver remnant volume using ICG clearance Intraoperatively during Vascular Exclusion (ALIIVE), and Associated Portal vein Embolization and Artery Ligation (APEAL), the first two are mostly used in HC [15].…”
mentioning
confidence: 99%